A Possible Role for Singlet Oxygen in the Degradation of Various Antioxidants. A Meta-Analysis and Review of Literature Data - Athinoula L. Petrou; Petros L. Petrou; Theodoros Ntanos; Antonis Liapis (MDPI AG, 2018)
The thermodynamic parameters Eact, ΔH≠, ΔS≠, and ΔG≠ for various processes involving antioxidants were calculated using literature kinetic data (k, T). The ΔG≠ values of the antioxidants' processes vary in the range 91.27-116.46 kJmol−1 at 310 K. The similarity of the ΔG≠ values (for all of the antioxidants studied) is supported to be an indication that a common mechanism in the above antioxidant processes may be taking place. A value of about 10-30 kJmol−1 is the activation energy for the diffusion of reactants depending on the reaction and the medium. The energy 92 kJmol−1 is needed for the excitation of O2 from the ground to the first excited state (1Δg, singlet oxygen). We suggest the same role of the oxidative stress and specifically of singlet oxygen to the processes of antioxidants as in the processes of proteinaceous diseases. We therefore suggest a competition between the various antioxidants and the proteins of proteinaceous diseases in capturing singlet oxygen's empty π* orbital. The concentration of the antioxidants could be a crucial factor for the competition. Also, the structures of the antioxidant molecules play a significant role since the various structures have a different number of regions of high electron density.